ANALISIS ANATOMI FUNGSIONAL OTOT FLEKSOR DAN EKSTENSOR TERHADAP KONTROL GERAK PADA SENAM LANTAI DASAR : LITERATURE REVIEW - Maria Natalian Jaun; Anggraeni, Emayanti; Mukharrar Fadjri; Ryan Andika Watem (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Basic floor gymnastics requires optimal movement control through the integration of strength, balance, flexibility, and neuromuscular coordination. However, most studies have focused on competitive athletes and advanced skills, so comprehensive studies that integrate the functional anatomy of flexor and extensor muscles with movement control in basic floor gymnastics are still limited. This study aims to analyze the role of the functional anatomy of flexor and extensor muscles in movement control in basic floor exercises through a literature review approach. The methods used were a literature review with a meta-analysis and thematic analysis approach. Data sources were obtained from the Google Scholar, ScienceDirect, and PubMed databases with publications ranging from 2016 to 2025. A total of 15 relevant national and international scientific articles were analyzed based on research design, subject characteristics, and key findings related to neuromuscular function. The results of the study showed that flexor and extensor muscles work synergistically as agonist-antagonist pairs in producing postural stability, support strength, and movement coordination in basic skills such as rolling, handstands, and movement transitions. Parameters such as peak torque, neuromuscular efficiency, and co-activation index were found to be significantly correlated with performance quality and balance.